D’Future Tent / Ariff Hakimi Hasbullah … [et al.] - Hasbullah, Ariff Hakimi; Rozhan, Intan Shafiqah Adleena; Muhamad Ikbal, Ahmad Syahir; Azian, Nur Sarah Izzati (2022)
Designed for comfort and functionality in our mind, D’Future Tent is a marvellous equipment for everyone that is involved in outdoor activities such as camping, hiking, and fishing. Aside from typical functions of an outdoor tent such as waterproof materials, and protection against the sun, D’Future Tent is specially equipped with fabrics that can harvest the solar energy, power outlet for personal uses, comfortable inflatable mattress, trackable RFID system, and built-in ground heater. Our main target customers are campers and hikers thus, we gladly recommend everyone to buy our product. We are striving to make sure that the purchasing process will be much easier for everyone. We also plan to have the government endorse the D’Future Tent mainly from the Ministry of Tourism where they can provide these tents to tourists as a gesture of our country’s hospitality. The price of our product is RM3,000. Considering the features it has, it is relatively cheap for the price. It will be the bang for the buck compared to other traditional tents out on market. We are sure that we can gain a huge leverage on the market due to the uniqueness of our product. We expected to gain at least more than a quarter of the market share in the span of 5 years. Our company is registered as a private company which is entitled the Sdn. Bhd. as a which consists of four (4) members. Our nature of business is a start-up that aims on producing outdoor tents. Our business can be considered as a manufacturing business. Each member of the company holds important positions that are Executive Manager, Financial Manager, Marketing Manager, and Operational Manager.